ADDITION OF DIFFERENT CARBON SOURCES TO TOTAL DENSITY OF BIOFLOK BACTERIA IN THE MEDIA OF TIGER SHRIMP (Penaeus monodon) - nasmia nasmia; Abdul Rifai (Universitas Tadulako, 2020)
This research was conducted to assess different carbon sources' addition to heterotrophic bacteria's density in tiger prawn rearing media (Penaeus monodon). The research design used was a completely randomized design (CRD) consisting of 4 treatments and five replications with experimental treatments, namely: A (without giving a carbon source), B (carbon source molasses with a C/N ratio of 15: 1), C (source flour carbon with a C/N ratio of 15: 1) and D (a source of tapioca carbon with a C / N ratio of 15: 1). The test organism used was tiger shrimp PL-21 with a weight of ± 0.005 g, which was maintained with a stocking density of 100 fish / 50 liters of water for 30 days. During the maintenance of shrimp, it is given pellet type feed with a frequency of three times a day, as much as 3% of the shrimp biomass. Providing bacterial activation is carried out every ten days with organic carbon sources every day in the morning and evening. The results showed that the group of microorganisms identified as Bacillus sp. diatoms, ciliates, copepods, Paramecium sp., Synedra sp., and nematodes. Providing tapioca carbon sources resulted in the highest bacterial density (9.0  10⁷ CFU ml ). In comparison, the highest floc volume was produced by treatment with the addition of flour carbon sources (3.65 ml/l).